Zoneamento das áreas de risco de inundação na área urbana de Santa Cruz do Sul - RS - Menezes, Daniel Junges (2014)
The discussions and reflections about natural disasters and risk areas configuration increasingly appear as significant themes, whether in the media who report events relating to this matter, or in academia, where the processes, dynamics and relationships that occur in these spaces are discussed and thought, focusing on both the populations involved as environment in question. In this perspective, the theme "risk" is placed from the viewpoints of technical, social, economic, political, administrative and legal, where the management and mitigation from damage emerge as centralized element of discussions. The floods appear among the natural disasters that cause more damage to population health and patrimony, generating a large number of homeless and also as significant rate of fatalities, due to the direct effect of floods and secondary infectious diseases to disorders in water and sanitation systems. The floods appear among the natural disasters that cause more damage to population health and patrimony, generating a large number of homeless and also a significant rate of fatalities, due to the direct effect of floods and secondary infectious diseases to disorders in water and sanitation systems. In urbanized areas, floods are amongst the natural threats that cause the most natural and human damage. The phenomenon of intense urbanization and historic deficit in implementing appropriate and effective housing policies in Brazil, plus real estate speculation and the segregation process to which refers, has reduced the alternative of the population with the lowest income, that started to settle along the areas unfavorable geologically, without planning and infrastructure. This framework has contributed to the risk increase situations associated with fluvial dynamics. Amongst the demand to subsidies for management of these areas are the risk zonings that are emerging as a tool that seeks to give contribution to prevention and management of affected areas by floods and arise as management actions at the federal, state and municipal mainly, with the main objective of this research is to develop a zoning of risk associated with floods in the municipality of Santa Cruz do Sul. Were mapped susceptible areas to flooding and described and analyzed the occupied areas. The danger was associated by differences as severity of floods which vary as to recurrence, speed and destructive power of the process and also the affected area. The research allowed to establish a significant relationship between the urban pattern, the degree of intervention in drainage and the vulnerability for flood and consequently the presence of a higher or lower risk in distinct portions of urban area. The low-risk areas were associated with areas of a better urban pattern, lower recurrence or where interventions have minimized the possibility of extravasation of water courses. The medium risk areas are associated with areas very close to drainage that are perceptible interventions that minimize the possibility of extravasation and whose danger is a medium grade, and even in the most distant areas of drainages where these measures are less effective or missing. The high-risk areas were associated with portions where interventions are less mitigating, or missing and whose danger was established as high. The zoning of areas at risk of flooding pointed out as areas of very high risk, the allocated at south neighborhoods and irregular occupation in west of the urban area, characterized by high risk and very pegged to high vulnerability.